Comparative Effects of Sand- and Grass-Based Repeated-Sprint Training on Aerobic and Anaerobic Performance in Soccer Players. - Yan, Hao; Zhai, Haiting; Wang, Tingting; Wang, Duchun; Wei, Hongwen (Journal of Sports Science & Medicine, 2026)
This randomized controlled trial examined whether repeated-sprint training (RST) performed on sand or grass induces different adaptations in collegiate soccer players. Forty-two male players were randomly assigned to a sand-RST group (SAND, n = 14), a grass-RST group (GRASS, n = 14), or a control group (CON, n = 14). SAND and GRASS performed repeated-sprint training during two scheduled training sessions per week for six weeks, whereas CON completed standard technical soccer training of equivalent duration during the same two weekly sessions. All groups continued the same regular team training program, with the intervention delivered within two scheduled weekly sessions. Before and after the intervention, participants completed vertical jump tests including squat jump and countermovement jump, a running based anaerobic sprint test with peak, mean, and minimum power and fatigue index, and a graded treadmill test providing VO2max, anaerobic threshold, and running economy. Baseline-adjusted analyses were conducted to examine between-group differences (ANCOVA for outcomes meeting model assumptions; mixed-design ANOVA when assumptions were violated). These analyses showed significant Group by Time interactions for all jump and running based sprint variables and for VO2max and anaerobic threshold (p < 0.01), whereas the interaction for running economy was not significant (p = 0.15). Compared with GRASS, SAND showed greater improvements in squat jump (p < 0.01), mean power (p = 0.03), minimum power (p < 0.01), and fatigue index (p < 0.01). Aerobic adaptations were comparable between sand and grass, and no clear surface specific advantage was observed for running economy. In conclusion, implementing RST within scheduled team sessions improved jump performance, repeated-sprint performance indices, and aerobic fitness in collegiate soccer players, while sand-based training may provide greater benefits for squat jump and selected outcomes related to repeated-sprint fatigue resistance.